Geographic influences and their interaction with the development process in Tartous Governorate. - سعود, ربى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The geographical factors available in any region play an important and vital role in helping to revive the socio-economic development process, as the available natural factors have an essential and important role, and this factor is coupled with the demographic characteristics of the population and its development to the extent that it becomes an auxiliary and essential element, because of the positive developments it represents, in addition to other service and economic factors. This research works to highlight these factors in Tartous Governorate and their role in the development process